Nilai Sosial Ekonomi Sutera pada Masyarakat Pakkana Kabupaten Wajo - Andi Nursida (Universitas Muhammadiyah Makassar, 2017)
The purpose of this study is to determine the socio-economic impact of the existence of silk weaving and professional composition in the community Pakkana Tanasitolo District Wajo District. The type of research uses qualitative research with data collection techniques using observation, interview and documentation. Data analysis techniques use qualitative decriptive with data reduction stages, data presentation, and conclusions. The results of this study indicate that (i) the impact of social values as everyday clothing and custom systems, as symbolic and distinctive identity for the Bugis community stratification system. (ii) Impact of economic value to supplement family income. The composition of Profession consists of farmers 17.92%, civil servants 1.43%, weaving traders 0.86%, weaving businessman 0.75%, weavers 17.13%, police or army 0.35%, driver 1.51% and others 66.16%.Keywords: Social Economics, Profession Composition